Taxonomic notes on two endemic species of Oberonia Lindl. from Western Ghats, India - Kiruthika, K; Sulaiman, M; Murugan, C (Plant Science Today, 2024)
The genus Oberonia is known for its micro floral arrangement. Due to its minute structure, excess of new species are reported. The present paper reveals the synonymization of two recently described species of the genus Oberonia viz. O. saintberchmansii and O. wynadensis under O. anamalayana and O. josephi respectively. The original illustration and live dissected images of the species are provided for easy identification.